Probability risk assessment of island operation event for large scale photovoltaic plant - Ivas, Mihovil; Marusic, Ante; Havelka, Juraj; Capuder, Tomislav (Automatika, 2019)
Original methodology for the calculation of island operation event occurrence possibility is proposed for the photovoltaic power plants connected to medium voltage grid. Within the methodology description, event fault tree with number of pairs of basic initial events is discussed, where probability for the basic events are defined and flow chart for the proposed calculation is given. The novelty in the approach for probability calculation includes also proposal for development of frequency distribution functions for concerned power generation and consumption variables which have to be modelled for the probability calculations, for which the triangular distributions curves have been chosen. Being boundary conditions for definition of non-detected island event, borders of non-detection zones are defined for the common island detection protection functions: over frequency and under frequency, over voltage and under voltage and rate of change of frequency functions. Comparison of the island event probability is presented on case study example, with conclusion that standard voltage and frequency protection alone are not satisfying, but ROCOF protection could be suitable, subject to particular local grid characteristic and calculative verification of probability.